Pengaruh Influencer Marketing dan LifeStyle terhadap Perilaku Impulsive Buying di Platform E-Commerce pada Mahasiswa FEBI IBN Tegal - Nurul Fitri Habibah; Muhammad Arya Azizi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Advances in digital technology and the rise of e-commerce platforms like Shopee and TikTok are driving changes in consumer behavior, particularly among Generation Z, who are prone to impulsive buying. This behavior is fueled by marketing strategies such as influencer marketing and lifestyle strategies that attract spontaneous shopping. This phenomenon also occurs among FEBI students at the IBN Tegal Campus. Despite understanding the ethical principles of Islamic consumption, such as simplicity, balance, and avoiding wasteful behavior, they still engage in consumptive behavior. This study aims to examine the influence of influencer marketing and lifestyle on impulsive buying behavior. The research method used a quantitative approach with a sample of 53 respondents through Convenience Sampling. Data analysis used multiple linear regression using t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that influencer marketing has a positive and significant effect on impulsive buying behavior, with a calculated t-value of 2.271 > t-table 1.675 (sig. 0.000 < 0.05), and lifestyle has a calculated t-value of 4.430 > t-table 1.675 (sig. 0.000 < 0.05). Simultaneously, both variables have a positive and significant effect on impulsive buying behavior, with an F-value of 33.333 > F-table 2.79 (sig. 0.000 < 0.05). The coefficient of determination (R²) of 0.571 indicates that 57.1% of the variation in impulsive buying behavior is influenced by these two variables. Although students understand Islamic economic values, including consumption ethics that prioritize needs over wants, in practice, consumptive behavior still occurs. This indicates a gap between students' knowledge and consumption behavior in the context of sharia.